Multiresponsive micellar block copolymers from 2-vinylpyridine and dialkylvinylphosphonates with a tunable lower critical solution temperature. Issue 82 (18th August 2016) - Adams, F.; Altenbuchner, P. T.; Werz, P. D. L.; Rieger, B.
Abstract : Tailor-made, multi-responsive micellar AB and ABB′ block copolymers show a pH-sensitivity and a tunable LCST within an expanded temperature range. Abstract : AB and ABB′ block copolymers were synthesized with a 2-methoxyethylamino-bis(phenolate) yttrium catalyst. 2-Vinylpyridine and diethylvinylphosphonate were chosen to obtain amphiphilic blockcopolymers. The obtained tailor made, so far unexplored and multi-responsive polymers self-assemble to form micelles and show a pH-sensitivity and a LCST. To tune the LCST other dialkylvinylphosphonates were incorporated leading to a shift of the LCST.